Interactive Infographics' Effect on Elaboration in Agricultural Communication - Erin Burnett; Jessica Holt; Abigail Borron; Bartosz Wojdynski (Journal of Applied Communications, 2019)
In public health, politics, and advertising, interactive content spurred increased elaboration from audiences that were otherwise least likely to engage with a message. This study sought to examine interactivity as an agricultural communication strategy through the lens of the Elaboration Likelihood Model. Respondents were randomly assigned a static or interactive data visualization concerning the production of peaches and blueberries in Georgia, then asked to list their thoughts in accordance with Petty and Cacioppo’s thought-listing measure. Respondents significantly exhibited higher elaboration with the interactive message as opposed to the static, extending the results of past research in other communication realms to agricultural communication as well. This increase in attitude and cognition encourages agricultural communicators to pursue the use of more interactive elements in their messaging.
Keywords: interactivity; agricultural news; interactive graphics; attitudes; elaboration